(untitled) (International Journal of Business, Economics and Management, 2018)
The aim of this research is to examine the effect of innovation strategy on firm’s performance and investigate the moderating effect of ownership structure and board of directors’ characteristics, as governance attributes, on this relationship. Based on a sample of 29 Tunisian companies over a period from 2008 to 2013, we show that innovation strategy has no effect on firm’s performance. However, some corporate governance attributes are likely to affect this relationship which turns significant. Overall, the independence of board members, CEO duality, audit quality and the independence of audit committee members have moderating effects on the relationship between the innovation strategy and performance. These results illustrate the crucial role played by the board of directors in determining the relationship between the innovation strategy and firm performance.